Application of The Rules-in-Use Concept in the Analysis of Regulations on Forest and Land Rehabilitation (Reforestation) - Rizki Sukarman Sawaka; Bramasto Nugroho; Iin Ichwandi; Budhy Setiawan (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesia faces the problem of forest degradation, with Forest and Land Rehabilitation (FLR) being one of the key efforts undertaken to address it. This study analyzes the formal institutional framework governing FLR implementation in Indonesia using the Institutional Analysis and Development (IAD) Framework, focusing on Ostrom’s concept of rules-in-use. Content analysis was conducted on four main regulations: Law No. 41 of 1999, Government Regulation No. 26 of 2020, Minister of Environment and Forestry Regulation No. P.2 of 2020, and Minister of Environment and Forestry Regulation No. P.23 of 2021. The findings show that seven types of institutional rules, position, boundary, choice, aggregation, information, scope, and payoff rules, are included in these regulations, but they are not yet fully synchronized. The distribution of roles among actors remains overlapping, coordination mechanisms are weak, and incentive rules are not clearly defined. Moreover, the regulations tend to emphasize administrative and physical aspects of planting rather than ecological and social outcomes. Weaknesses in this rules-in-form structure create unstable action arenas and reduce policy effectiveness. This study highlights that the success of FLR is determined not only by technical aspects but also by the clarity and consistency of formal rules. Harmonization of regulations, strengthened cross-actor coordination, and transparency of information are needed to ensure that FLR implementation supports the sustainable restoration of the forest’s ecological and social functions